Polyacids self-dissociation model - Neto, Augusto Agostinho [UNESP]; Drigo Filho, Elso [UNESP]; Fossey, Marcelo Andrés [UNESP]; Neto, João Ruggiero [UNESP] (American Chemical Society (ACS), 1997)
This work deals with a model to interpret pH measurements of solutions of weak rodlike polyacids, in the absence of added salts or titrating base. The polyacid is modeled as a series of point charges discretely distributod in a straight line with a distance of closest approach for the protons and an average distance between dissociable monomers, projected in the polymer chain axis. Aside from these two geometrical parameters, the dissociation constant for the isolated monomer that describes the proton dissociated monomer interaction forms the basis of the model. The assumption of cylindrical symmetry and the adoption of the cell model lead to a form written in terms of elementary functions for the mean electrostatic potential. Values of pH (related to the proton concentration in a region beyond the influence of the polyacid) as a function of polymer concentration are displayed graphically for some values of the geometrical parameters and of the dissociation, constant. Theoretical predictions of pH values as a function of polymeric concentration are compared with measured values for poly-L-glutamic and polygalacturonic acids, and a good agreement is found. Theoretical values for the dissociation degree in terms of polymeric concentration are shown for the two experimentally investigated systems. These values are in a range appreciably smaller than what is usually studied as a result of titration.
Keywords: Composition effects; Dissociation; Electrostatics; Mathematical models; Monomers; pH effects; Polymers; Protons; Dissociation constant; Polyacids; Acids